Épidémie de fake news. Figuration d’une viralité dysphorique - Elise Schürgers (MediAzioni)
This article aims to shed light on the discursive representations of the virality of fake news in the daily broadsheet newspapers in France and French-speaking Belgium (2016-2019). Following the perspective of “enunciative pragmatics of figures of speech” (Bonhomme 2014), the analysis focuses on the various metaphorical networks of virality that surround the development of the phrase fake news as formula (Krieg-Planque 2003; 2009). We first identify two metaphorical frameworks conventionally attached to virality: contagion and military struggle. These seem to operate in a complementary manner, paving the way for interdiscursive coherence. We then turn to a particular case — that of virality as “triumph” — which invites us to consider what is projected to the forefront of representation and what, conversely, is blurred or presupposed. The analysis leads us to believe that representations of virality via these two sets of metaphors (one routinized, the other more context-dependent) have not only played a key role in helping the Anglicism to become a formula in the francophone public sphere, but have also served to reinforce a presupposition that deserves to be questioned: that exposure to media objects is equivalent to passive permeability to those.